Dental restorative materials and special consideration for the elderly - Mohammed Ali Alakkad, Tarik; Diwan, Moayad Adnan; Sanie, Mohammed Khalid Al; Balkhair, Ola Jamal; Al Mobarak, Faisal Musaad; Badahdah, Rasha Ahmed; Bakhsh, Abdulaziz Fahad; Otaibi, Norah Rjaa Al; Abdulwahed, Saud Fahad Al; Sharif, Haifa Mohammed Al; Anazi, Riyadh Obied Al (International Journal Of Community Medicine And Public Health, 2023)
With the global population aging, the oral health of elderly individuals faces unique challenges, particularly concerning dental caries. Root caries, in particular, have become a growing concern due to the significant number of retained teeth in older adults. This review delves into the frequency of root caries among older individuals and examines the limitations of existing dental restorative materials, including amalgam, glass ionomer cement, and light-cured composite resin, in meeting the unique requirements of the elderly. It underscores the urgent necessity for improving the antibacterial, bonding, remineralization, strength, and durability characteristics of these materials. Additionally, the study discusses factors related to aging, treatment planning, and special considerations in geriatric dental care. The review also delves into the challenges associated with providing dental care to elderly individuals, including depression, postural hypotension, prescribed drugs, delayed healing, adaptive potential, mucosal quality, and poor plaque control. Moreover, it addresses the role of xerostomia, bruxism, and certain medical conditions in exacerbating dental issues in the elderly. It also introduces novel anticariogenic restorative materials, such as antimicrobial materials, remineralization materials, and self-healing/low-shrinkage materials, highlighting their potential to improve oral health in older individuals.